HARMONY AND SCALE ANALYSIS GUITAR PLAYING OF THE SONG KROMATIK LAGI BY DEWA BUDJANA - Firdaus, Taufiqurrihan; Rizki Harmono Sejati, Irfanda (Jurnal Penelitian Musik, 2023)
This study aims to analyze the harmony and scales in guitar playing by Dewa Budjana in his work entitled Kromatik Lagi. The thing that is focused in this research is how tones that are outside the ionian scale can be included in an interesting work. The research method used is a qualitative method with an analytical description approach that refers to the Miles and Huberman model. The data collected is in the form of sheet music that will be discussed per beat and there are a total of 20 beats that include intro and theme. This research only examines the intro and theme sections. It can also be concluded that the work Kromatik Lagi by Dewa Budjana is not playing with origin. But based on some music theory so that it can include chromatic notes that are heard if played in sequence the tone sounds dissonant or disturbing.